Advancing Social-Emotional Learning in Elementary Education: Exploring Implementation, Inclusivity, and Long-Term Impact - Ibanga, Isaac John; Yusuf, Mohammed Adamu; Umoru, Mohammed Lawal (The Indonesian Institute of Science and Technology Research, 2024)
Social-emotional learning (SEL) has become a crucial component of student development, increasingly recognized for its positive impacts on both academic success and life outcomes. However, challenges remain in effectively implementing SEL programs across diverse educational settings, particularly in addressing the needs of marginalized and minoritized students. This study explores the integration of AI tools in the literature review process to examine current practices, effectiveness, and gaps in SEL programs. A literature review was conducted using various artificial intelligence applications, including Elicit AI, ChatGPT, and Google Scholar. Relevant articles were identified based on thematic focus and retrieved from credible academic sources. These articles were analyzed for thematic clusters using ChatGPT, and a word cloud was generated to identify supporting keywords. The analysis revealed several key factors critical to successful SEL program implementation: teacher competency, developmentally appropriate skill-building, and nuanced measurement techniques. The study also highlighted the need for more inclusive SEL programs that cater to the diverse needs of marginalized students. Evidence showed that SEL programs have a positive return on investment, contributing to both academic performance and long-term success.